Coup d'État, authoritarism and transition: A comparative analysis of Brazil and Chile - Aggio, Alberto [UNESP] (Editorial Universidad de Sevilla, 2015)
This article aims to accomplish a comparative analysis of Brazilian and Chilean political histories parting from the moment both countries experienced breaks in the democratic constitutional order, in Brazil, on 1964 and in Chile, on 1973. The article initiates about the utilization of comparison in political history studies in order to define an interpretative board concerning the conjunctures that preceded the coups d'État and, then, discuss about the main characteristics of the authoritarian regimes, analyzing especially the economic, social and political transformations that were occurring. It continues with the analyzes of the democratic transition process and its governments, in Brazil, from 1985, and, in Chile, on 1990. Lastly, it analyzes, comparatively, the reach as the deadlocks of both democratic experiences.
Golpe, autoritarismo e transição: Uma análise comparativa de Brasil e Chile
Keywords: Authoritarianism; Brazil; Chile; Comparative Political History; Democracy